2020
DOI: 10.1017/dmp.2020.204
|View full text |Cite
|
Sign up to set email alerts
|

Awareness Among Undergraduate Students of Mangalore City Regarding Novel Coronavirus (COVID-19): A Questionnaire Study

Abstract: Background: COVID-19 outbreak has surfaced as an imminent threat for the public health. Since India is a populous country, it is important for Indians to be aware of the basic modes of prevention that can diminish the spread of the COVID-19 infection. Aim: The present questionnaire study was carried out among the undergraduate students to assess the awareness regarding the spread and control of COVID-19. Methods: The questionnaire was circulated among the undergraduate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
18
1
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 6 publications
7
18
1
4
Order By: Relevance
“…Compared to medical and non-medical students in Jordanian universities, dental students' scores in this sample were very close in knowledge questions about symptoms and mode of transmission; however, they were more aware of the absence of any vaccination for COVID-19 and the ineffectiveness of antibiotics in managing COVID-19 [19]. In addition, students in the current sample agreed with medical students in Jordan and non-medical disciplines in India on the importance of handwashing as an essential measure to prevent COVID-19 transmission; however, students in this sample selected wearing masks also as an important measure [20,21]. This is expected given the time our data was collected, when more robust evidence on mask-wearing was emerging [5].…”
Section: Discussionmentioning
confidence: 72%
“…Compared to medical and non-medical students in Jordanian universities, dental students' scores in this sample were very close in knowledge questions about symptoms and mode of transmission; however, they were more aware of the absence of any vaccination for COVID-19 and the ineffectiveness of antibiotics in managing COVID-19 [19]. In addition, students in the current sample agreed with medical students in Jordan and non-medical disciplines in India on the importance of handwashing as an essential measure to prevent COVID-19 transmission; however, students in this sample selected wearing masks also as an important measure [20,21]. This is expected given the time our data was collected, when more robust evidence on mask-wearing was emerging [5].…”
Section: Discussionmentioning
confidence: 72%
“…3 Another study conducted by Das et al among undergraduate students in Mangalore city found awareness regarding COVID-19 pandemic was 98.3% which was quite similar with results of our study. 4 Difference in awareness can be attributed to different educational status among study participants and method by which the studies were conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Das et al reported that 96% of their study subjects were aware about the way infection spreads. 4 Kebede et al found that 95% of study participants were aware about the way infection spreads. 5 Similarity in results between our and other studies shows that public gets information about coronavirus through any media or through various approaches used by Government to spread awareness about the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Por la disponibilidad y mayor accesibilidad, las fuentes de información digitales van cobrando mayor auge en los últimos tiempos, sin descartar las fuentes tradicionales. En este sentido se observó que, según Khasawneh et al (5) , el 87% de sus estudiantes encuestados utilizan motores de búsqueda en línea y redes sociales como fuente de información, cifras semejantes a las encontradas por Olaimat et al (11) con 93%; Das et al (14) con 88.7%; Olum et al (11) del 79%; mientras que en nuestro estudio solo el 45 % del estudiantado busca información en redes o en motores de búsqueda, reflejando una cifra menor a las mencionadas por los anteriores autores y evidenciando la utilización de artículos científicos, sitios oficiales y comentarios médicos como fuentes de información consultadas con mayor frecuencia.…”
Section: Discussionunclassified
“…Los estudiantes de medicina, como trabajadores de atención médica de primera línea, son más susceptibles a ser infectados por el virus (10)(11)(12)(13) . Diversos grupos de estudiantes de medicina, fueron capacitados sobre los pasos adecuados que deben seguirse en el lavado de manos, por ejemplo, como una de las medidas más simples y eficaces para la prevención del contagio (14)(15)(16)(17) . Dado que existe la posibilidad de crisis del personal de atención durante la pandemia de COVID-19, el sistema de atención podría incorporar estudiantes de medicina avanzados para fortalecer el número de personal sanitario.…”
Section: Introductionunclassified